Investment and investment process: genesis and modern approach - D. A. Dzhioev (Вестник университета)
The article considers various domestic and foreign approaches to the interpretation of the concept of «investment» as an economic category in retrospect (historical analysis of the origin and development of investment theory) and at the present stage of development. Based on the critical analysis of various interpretations, the paper formulates the author’s definition of the concept of «investment». In turn, investment, as one of the most important elements of the economy, is the basis for the development of territories characterized by the level of development of investment processes in them. The article analyses various interpretations of the concept of «investment process», carries out their systematization, and proposes the author’s definition of the concept. The research uses methods of bibliographic and logical analysis as well as a systematic approach.